The media studies toolkit - Newman, Michael Z. (Routledge, an imprint of the Taylor & Francis Group, 2022)
"In this critical primer, Michael Z. Newman introduces newcomers to the key concepts, issues, and vocabulary of media studies. Across ten chapters, Newman examines topics from text and audience to citizenship and consumerism, drawing on a myriad of examples of media old and new. Film and TV rub shoulders with mobile games and social media, and popular music and video sharing platforms with journalism and search engines. While the book takes a critical, cultural approach, it covers topics that apply across many kinds of media scholarship, bridging the humanities and the social sciences and looking at media as a global phenomenon. It considers media in relation to society and its unequal structures of power, and relates media representations to their conditions of production in media industries and consumption in the everyday lives of audiences and users. Spanning the historical periods of mass media and online participatory culture, it also probes assumptions about media that were formulated in a previous era and looks at how to update our thinking to address an ever-changing digital mediascape. With its clear and accessible style, this book is tailor-made for undergraduate students of media, communication, and cultural studies, as well as anyone who would like to better understand media"--Provided by publisher.